At world time, on the Plane of Immanence. A Reading of Sistema Nervioso by Lina Meruane - Navarro Morales, Marcelo (2024)
This paper analyzes Lina Meruane’s novel, Sistema Nervioso (2018), from the perspective of the notion of the plane of immanence proposed by Deleuze and Guattari (1997). By virtue of the alibi provided by the narrative plot, the intra/extradiegetic narrators of this novel slide from the plane of organization of substantial forms to the plane of consistency of unstable and unformed matter. The plane of immanence, which groups these planes, allows them to see and think about the aberrant zones of communication between kingdoms, genders and species; to attend to the coexistence and simultaneity of diverse temporalities and scales of time and space; and allows them to approach the complex crossroads that the contemporary world faces.